Developing a self-determination motivation scale for English learners with Chinese background - Chiang, Juiching (Frontiers in Education, 2024)
Interest" is one of the most important factors that trigger English learning behavior, and self-determination theory believes that "interest" and "value" are important factors associated with target behavior. Therefore, the purpose of this study is to construct and establish a "Self-Determination Motivation Scale of English Learner" based on the core concept of self-determination theory that is the three innate needs. There were 169 participants who were university students in different majors with Chinese background and taking English class in a university. The research tool is extracted from Learning Climate Questionnaire (LCQ) (6 questions on autonomy), Perceived Competence for Learning (PCS) (4 questions on competence), and Basic Psychological Needs (BPN) in General (8 questions on relatedness) and developed an 18-item questionnaire. The data were obtained by existing three different selfdetermination questionnaires and analyzed by Confirmatory Factor Analysis (CFA).The results show that after CFA, 15 items of the scale, which extracted from the existing three different self-made questionnaires, were maintained and the removed three items are all reverse items. Also, the reliability the developed 15-item scale is of .95. The conclusion is that the developed 15-item scale is more suitable for university English learners with Chinese background, although the existing three different selfdetermination questionnaires are still valid and reliable. Three suggestions for future research are to add expert validity for item review, adjust the number of reverse items, and have more participants to master scale. The implications, limitations, and future research plans are presented in this paper.